The marriage of surgical simulation and telementoring for damage-control surgical training of operational first responders: A pilot study. Issue 5 (November 2015) - Kirkpatrick, Andrew W.; Tien, Homer; LaPorta, Anthony T.; Lavell, Kit; Keillor, Jocelyn; Wright Beatty, Heather E.; McKee, Jessica Lynn; Brien, Susan; Roberts, Derek J.; Wong, Jonathan; Ball, Chad G.; Beckett, Andrew
Abstract : BACKGROUND: Hemorrhage is the leading cause of preventable posttraumatic death. Many such deaths may be potentially salvageable with remote damage-control surgical interventions. As recent innovations in information technology enable remote specialist support to point-of-care providers, advanced interventions, such as remote damage-control surgery, may be possible in remote settings. METHODS: An anatomically realistic perfused surgical training mannequin with intrinsic fluid loss measurements (the "Cut Suit") was used to study perihepatic packing with massive liver hemorrhage. The primary outcome was loss of simulated blood (water) during six stages, namely, incision, retraction, direction, identification, packing, and postpacking. Six fully credentialed surgeons performed the same task as 12 military medical technicians who were randomized to remotely telementored (RTM) (n = 7) or unmentored (UTM) (n=5) real-time guidance by a trauma surgeon. RESULTS: There were no significant differences in fluid loss between the surgeons and the UTM group or between the UTM and RTM groups. However, when comparing the RTM group with the surgeons, there was significantly more total fluid loss ( p = 0.001) and greater loss during the identification ( p = 0.002), retraction ( p = 0.035), direction ( p = 0.014), and packing( p = 0.022) stages. There were no significant differences in fluid loss after packing between the groups despite differences in the number of sponges used; RTM group used more sponges than the surgeons and significantly more than the UTM group ( p = 0.048). However, mentoring significantly increased self-assessed nonsurgeon procedural confidence ( p = 0.004). CONCLUSION: Perihepatic packing of an exsanguinating liver hemorrhage model was readily performed by military medical technicians after a focused briefing. While real-time telementoring did not improve fluid loss, it significantly increased nonsurgeon procedural confidence, which may augment the feasibility of the concept by allowing them to undertake psychologically daunting procedures. Abstract : Supplemental digital content is available in the text.